Strategi Kepemimpinan Kepala Sekolah dalam Membangun Pendidikan Humanistik Berbasis Teknologi di Era Society 5.0 - Fitria Deswanda; M. Imamul Muttaqin (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
The era of Society 5.0 presents both challenges and opportunities for the education sector to integrate technology with humanistic values. Technology-based humanistic education focuses on developing students' character, emphasizing ethics, creativity, and adaptability, while also making wise use of technology. In this context, school principals play a strategic role as leaders who guide the transformation of education to align with the demands of the times. This study aims to analyze the leadership strategies of school principals in building technology-based humanistic education using a qualitative approach with a literature review method. Data was gathered from various sources, such as journals, books, and relevant documents. The findings reveal that the leadership strategies of school principals include empowering teachers in technology literacy, strengthening the humanistic culture in schools, and utilizing technology as a tool to support an inclusive learning process. This research provides strategic recommendations for school principals to optimize their roles in building an innovative, humanistic, and relevant education system in the Society 5.0 era.